(untitled) ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2017)
Background: Six-Sigma is a quality improvement strategy that provides a clear roadmap for organizations to deliver nearly perfect products and services. In an increasingly knowledge intensive and global economy, superior management of human capital- the skills, talents and knowledge of an organisation’s employees is arguably the only sustainable source of competitive advantage for an organisation. Objective: To assess the effectiveness of Six-Sigma and examine its impacts on various performance measures in hotels, seeking for what values and benefits it brings to improve the overall performance of human capital. Methodology: The survey was circulated to a panel of prominent academics and Hotel professionals in the field of quality management to capture their feedback as a part of a pilot survey. The respondents were asked to rank the 10 key drivers needed for the successful deployment of Six-Sigma on a scale of 1-5 Results: Only 31% of these hotels were actively involved in a documented Six-Sigma project. Four hotels are planning to implement Six-Sigma in the near future. The results of the study also revealed that the most commonly used Six-Sigma metrics is the number of customers’ complaints. This metric is followed by defect rate and process capability. Human Capital Performance scores give an indication that hotels implementing Six-Sigma have achieved more benefits as compared to other hotels implementing other quality management programs. Conclusion: Six Sigma need to well propagate among hospitality sector so that its benefits can help improve customer satisfaction.